A Comparative Study of English-Speaking Problem Among Freshmen and Senior English Education Students - Ghafira Anatiaz Putri; agung Dwi Nurcahyo; Aisyah Ririn Perwikasih Utari (Prominent, 2026)
In language education, students develop four language skills: speaking, writing, listening, and reading. Speaking is one of the four language skills. From freshmen to seniors, they all experience difficulties in learning English. Some of the problems may change, some may stay the same, and some may even be more complex than before. The aim of this research is to explore the differences and similarities of speaking problems faced by freshmen and senior students of English Education Department in Muria Kudus University. The methodology of this research was qualitative method. To collect the data, the researcher used questionnaire and interview. The questionnaire was distributed to freshmen and seniors that consisted of 15-20 participant. While the interview was conducted with 2 freshmen and 2 seniors from the questionnaire. Based on the data obtained, there were some similarities of problems such as affective problem, lack of consistent speaking partner, and underutilization of department programs. There were also some differences found such as cause of anxiety, finding opportunity to practice their English, vocabulary knowledge, and grammar knowledge. With that conclusion, the researcher made some suggestion, namely for lecturers to assist students in managing their anxiety and encourage them to optimize the programs provided by the departments. For freshmen to expand their knowledge and practice their speaking more. For seniors to keep practicing their English and expanding their vocabulary and grammar further. For future researcher to use this research as a useful resource in the future. Keywords: freshmen, seniors, speaking problems